Design of the Web Interface to Manage Automatically Generated Production Documentation - Martin Pollák (TEM Journal, 2018)
Automation of production activities allows us to create a complex product life cycle with help of CAx systems, automation of NC programmes creation being a part of it. There are some cases for which it is not necessary to create complex production procedures. In such cases making of production documentation comes into discussion. However, process documentation does not fulfil all the requests by operators of NC machines. For NC machine operators, the most appropriate form of reports is that it allows not only convenient search of information on the PC, but also a comprehensive printed form, which together with the NC program and the production drawing would constitute the accompanying documentation necessary for the production of the component. The article describes the creation of a web interface used to manage and archive data generated by creation in the PTC Creo environment supplemented by a number of additional information and data on the collected items needed for the production of components by the operators.